ANALISIS PERILAKU SEX REMAJA SMAN 14 BANDARLAMPUNG 2011 - Iskandar Iskandar; Nurhikmah Nurhikmah; Asmi Erlita (Holistik Jurnal Kesehatan, 2019)
ABSTRACT: INFLUENCE OF TRAINING PROGRAMS: PERFORMANCE ASSESSMENT SYSTEMS (PAS) AND PRACTICE AMONG HEAD NURSES PERFORMANCES AT ATMA HUSADA MAHAKAM HOSPITALPROVINCE OF EAST KALIMANTAN Background: The head nurse plays a role in the performance appraisal system, objectively assessment resulting satisfaction on the staff nurse performance. Through training programs: performance assessment systems (pas), the head nurse could improve assessment systems to staff nurse Purpose: Knowing that the influence of training programs: Performance Assessment Systems (PAS) and practice among head nurses performances at Atma Husada Mahakam Hospital-Province of East Kalimantan Methods: This study used quasi experiment and approached one group pre test-post test design. The sample of 9 nurses (head nurse), measuring instrument used a questionnaire by univariat and bivariat analysis. Results: Show influences of training programs: Performance Assessment Systems (PAS) and practice among head nurses performances at Atma Husada Mahakam Hospital-Province of East Kalimantan with p-value=0.019. Conclusion: Based on this study suggested to hospital management to implementation of the Performance Assessment Systems (PAS) and improves the ability and skills of the head nurse in performing the assessment function.Pendahuluan: Kepala ruangan berperan dalam sistem penilaian kinerja dapat berjalan dengan baik dan tepat sehingga dapat memberikan kepuasan kepada perawat pelaksana. Pemahaman dan implementasi sistem penilaian kinerja yang dilakukan kepala ruangan dapat dilakukan melalui pelatihan. Tujuan: Mengidentifikasi pengaruh pelatihan sistem penilaian kinerja terhadap kemampuan kepala ruangan menerapkan sistem penilaian kinerja.  Metode: Penelitian ini menggunakan metode Quasi Experiment dan menggunakan pendekatan one group pretest -posttest design. Sampel berjumlah 9 orang kepala ruangan.Alat ukur yang digunakan kuesioner dengan analisis univariat dan bivariat. Hasil : Menunjukkan bahwa ada perubahan kemampuan kepala ruangan dalam menerapkan sistem penilaian kinerja sebelum dan sesudah pelatihan (ρ=0,019). Kesimpulan :  Berdasarkan penelitian ini disarankan agar kepala ruangan mengoptimalkan pelaksanaan sistem penilaian kinerja secara terprogram dan meningkatkan kemampuan dan keterampilan kepala ruangan dalam melaksanakan fungsi penilai.